Involvement of Annexin A2 Expression and Apoptosis in Reverse Polarization of Invasive Micropapillary Carcinoma of the Breast - Kazumori Arai; Tomohiro Iwasaki; Chinatsu Tsuchiya; Akihiro Sonoda (Case Reports in Pathology)
Invasive micropapillary carcinoma (IMPC) is characterized by pseudopapillary tumor-cell clusters with a reverse polarity (RP) floating in lacunar spaces, with aggressive biological characteristics. The RP prevention is considered to inhibit IMPC, but its pathogenic mechanisms remain unclear. Annexin A2 (ANX A2), a cell-polarity protein, is known to be involved in lumenogenesis. ANX A2 expression is immunohistochemically examined, as well as both epithelial membrane antigen (EMA) and mucin-1 glycoprotein (MUC-1), the gold-standard markers for luminal differentiation, in the background tumor components of a case of IMPC. The following findings were noticed: (1) Apoptosis was scattered with peripheral apoptotic vacuolar change; (2) EMA and MUC-1 expressions were found, rimming the peripheral apoptotic vacuoles (including the contact surface with neighboring tumor cells), and these positions corresponded to the ones with a distinct ANX A2 positivity; and (3) partially detached tumor cells showed distinct positivity of three proteins at the stroma-facing surface, which is consistent with a RP. Taken together, frequent apoptosis in tumor cells with membranous accumulation of ANX A2 is considered to be indispensable for the reverse polarization of IMPC, and that secondary necrosis following apoptosis induces the cell-polarity disorder and creates detached tumor cells with a RP.